2016
DOI: 10.1074/jbc.m116.727404
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis-like Neuronal Cell Death Caused by Cellular Cholesterol Accumulation

Abstract: Edited by Paul FraserAberrant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…For example, amine-modified polystyrene nanoparticles accumulate in lysosome, and induce LMP, resulting in induction of cell death [ 40 ]. In addition, l -norephedrine, a sympathomimetic amine, induces intracellular cholesterol accumulation in lysosome, and increases lysosomal vacuolization [ 41 ]. Yuan et al reported that accumulation of cholesterol oxidation products in lysosome induces vacuolization and increases lysosomal damages, which plays a critical role in cell death in macrophage [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, amine-modified polystyrene nanoparticles accumulate in lysosome, and induce LMP, resulting in induction of cell death [ 40 ]. In addition, l -norephedrine, a sympathomimetic amine, induces intracellular cholesterol accumulation in lysosome, and increases lysosomal vacuolization [ 41 ]. Yuan et al reported that accumulation of cholesterol oxidation products in lysosome induces vacuolization and increases lysosomal damages, which plays a critical role in cell death in macrophage [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We note also that this feedback would operate when cholesterol increases due to enhanced synthesis. It should not be functional in conditions of defective extrusion (Djelti et al., ) or dysfunctional lysosomal storage (Funakoshi, Aki, Tajiri, Unuma, & Uemura, ).…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective potential of Nec-1 and its analogs in cellular and animal models of ischemia is rather well supported (Chavez-Valdez et al 2012Degterev et al 2005;Li et al 2018;Ni et al 2018;Northington et al 2011;Xu et al 2010a;Yang et al 2017a;Yin et al 2015;Zhan et al 2019;Zhang et al 2016). Moreover, in an in vitro setting, Nec-1 attenuated the neuronal cell damage induced by various harmful agents, e.g., oaubain, glutamate (Glu), N-methyl-D-aspartate (NMDA), 6hydroxydopamine (6-OHDA), rotenone, 1-methyl-4phenylpyridinium ion (MPP+), methamphetamine, aluminum (Al), 24(S)-hydroxycholesterol, cholesterol, staurosporine, and doxorubicin (Funakoshi et al 2016;Ito et al 2017;Jantas et al 2014a;Li et al 2011;Wang et al 2014;Wu et al 2015;Xiong et al 2016;Xu et al 2007;Yamanaka et al 2011;Zhang et al 2013). It should be noted that the protective effect of Nec-1 in the above studies was only partial, suggesting the participation of other than necroptosis cell death programs which can vary depending on the type of neuronal injury as has already been shown by in vivo (ischemia, traumatic brain injury, spinal cord injury, retina injury) and in vitro studies (e.g., Al-, iron-, 6-OHDA-, or β-amyloidinduced neurotoxicity) (Askalan et al 2015;Chinskey et al 2014;Dai et al 2013;Dong et al 2012;Liu et al 2014;Rosenbaum et al 2010;Qinli et al 2013;Wu et al 2015;Xu et al 2010a;Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 95%